The Penerapan Strategi Pembelajaran Reading Aloud dalam Meningkatkan Hasil Belajar pada Pembelajaran Tematik Muatan Bahasa Indonesia Siswa Kelas I B MI Negeri 2 Pangkal Pinang - Tantri, Tantri (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2022)
This research is the result of studies and observations of the results of student learning by considering the learning process without using Reading Aloud Learning Strategy with learning using Reading Aloud Learning Strategy. This type of research is classroom action research (Classroom Action Research), using qualitative descriptive approach, this study aims to find out about implementation of Reading Aloud Learning Strategies, and improving learning outcomes students after using the Reading Aloud Learning Strategy on Thematic learning of Indonesian language content on students' reading texts in class I B MI Negeri 2 Pangkalpinang in Pangkalpinang. The data analysis is conducted by describing or explaining conditions associated with research objectives, how to calculate results the value obtained by students during the learning process, percentage and presentation of tables and figures related to variable conditions research such as the average value of students, the number of students who completed, the number of students who did not complete, the percentage of completeness was minimal, the activeness of students following lessons in each cycle. The results of the analysis present an increase in student learning outcomes in Thematic learning of Indonesian language content in reading texts and Cycles I and II using the Reading Aloud Learning Strategy. The results of this study indicate that the implementation of the Learning Strategy. Reading Aloud has been proven to improve student learning outcomes in learning Thematic content of Indonesian in the text reading material. It can be seen from the results of the average student learning, such as cycle I with an average of 65 (46.8 %), cycle II is 78.1 (96.8%).